Autonomic symptoms in patients with moderate and severe chronic obstructive pulmonary disease. Issue 3 (4th May 2018) - Mohammed, Jibril; Derom, Eric; De Wandele, Inge; Rombaut, Lies; Calders, Patrick
Abstract: Objectives: A synoptic description of the autonomic symptoms profile (ASP) of patients with COPD is not available. Therefore, we aimed to provide an overview of autonomic symptoms and its associates in COPD. Methods: We evaluated 89 subjects with COPD (65 ± 7.3 years; 66 males; GOLD II-IV) with an equal number of age- and sex-matched control subjects by means of the composite autonomic symptom score (COMPASS 31) questionnaire, which assesses autonomic symptoms across six domains (orthostatic intolerance, vasomotor, secretomotor, gastrointestinal, urinary and pupillomotor). Lung function, medication use and health status variables (quality of life: physical/mental component summary [PCS/MCS], fatigue, anxiety, depression and dyspnea levels) were also assessed. Results: Compared to controls, all subjects with COPD reported significantly higher orthostatic intolerance, secretomotor and total autonomic symptom scores ( p  < .05). Additionally, subjects with moderate COPD also reported significantly higher scores for vasomotor, gastrointestinal, urinary and pupillomotor symptoms compared to controls ( p  < .05). Nevertheless, these symptoms were comparable between the moderate and severe COPD subgroups ( p  > .05). The COPD subjects had poorer health status compared to controls as exhibited by significantly higher scores for depression, anxiety, fatigue and dyspnea, and lower scores values for PCS and MCS scores ( p  < .05). These health status variables were mildly associated with autonomic symptoms (0.214 ≤  r  ≥ 0.421; p  < .05), but not with demographic and lung function ( p  > .05). The MCS was the only significant predictor of total autonomic symptoms score in COPD ( p  = 0.001; β  = −0.430). Conclusion: Autonomic symptoms are present in all domains of the COMPASS-31 in COPD, irrespective of disease severity and demographic variables. Autonomic symptoms in COPD were mainly influenced by poor mental health.